On the Take: How Medicine's Complicity with Big Business Can Endanger your Health - Valéria Cavalcanti Rolla; Marilia Santini de Oliveira (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2008)
USA: Oxford University Press; 2004 ISBN: 978-0195176841